Improving English Pronunciation with AI Speech-Recognition Technology - Abimanto, Dhanan; Sumarsono, Wasi (Acitya: Journal of Teaching and Education, 2024)
This study explores the use of AI technology in the Google Read Along application as a tool to improve English pronunciation, particularly for students who struggle with English pronunciation. Therefore, the purpose of this study is to evaluate the Google Read Along app's effectiveness in improving English pronunciation, analyze the students' responses to using Google Read Along, and discover the factors that help students succeed in improving their pronunciation. Read Aloud is used in conjunction with AI technology to help children learn by listening to and precisely repeating new words and phrases. A quasi-experimental method was used to collect data, with 35 students in the experimental group and 35 in the control group. A questionnaire was presented to the experimental group regarding how they responded to Google Read Along, and interviews were conducted as further information to identify the factors affecting their pronunciation improvement. The results of the N-Gain test show that the Google Read Along is efficient in helping students improve their English pronunciation when used in combined with the Read Aloud approach by an average of 65.73 percent. As a result, a teaching strategy that combines the Read Aloud method and AI Google Read Along can be an effective alternative. Additionally, the instant feedback offered by this application gives students a chance to recognize their errors directly, and the convenience of using the application for learning anytime anywhere has a significant impact on their success in improving their pronunciation.